PROACTIVE PERSONALITY AND CAREER DECISION-MAKING SELF-EFFICACY: THE MEDIATING ROLE OF CAREER ADAPTABILITY IN VOCATIONAL HIGH SCHOOL STUDENTS (International Journal of Cultural and Social Science, 2026)
A This study aims to analyze the effect of proactive personality on career decision-making self-efficacy, with career adaptability as a mediating variable among students of SMK Negeri 1Portibi. The study involved 376 respondents selected as the research sample. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships among variables. The results indicate that proactive personality has a positive and significant effect on career decision-making self-efficacy, suggesting that higher levels of proactive personality are associated with greater confidence in making career decisions. In addition, proactive personality significantly influences career adaptability, indicating that students with proactive characteristics are better able to adjust to career-related challenges and changes. Furthermore, career adaptability has a positive and significant effect on career decision-making self-efficacy, implying that stronger adaptability enhances students’ confidence in determining their career paths. The findings also reveal that career adaptability serves as a significant mediating variable in the relationship between proactive personality and career decision-making self-efficacy. This indicates that proactive personality can enhance career adaptability, which in turn strengthens self-efficacy in career decision-making. Therefore, efforts to improve students’ career decision-making self-efficacy can be effectively achieved by simultaneously developing proactive personality and career adaptability.